The Effectiveness of Psychoeducation and Mind Mapping in Preventing Early Marriages in Central Java, Indonesia - Eviyati Aini Muriana; Mardiyono Mardiyono; Lanny Sunarjo; Melyana Nurul Widyawati (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
During the COVID-19 pandemic, the number of early marriages increased. Early marriage causes biological and psychological problems in the mother and her baby. The combination of psychoeducation and mind mapping emerged as a preventive effort against early marriage. The aim of this study was to analyze the effectiveness of this combination in preventing early marriage in West Java, Indonesia by influencing adolescents’ knowledge and intentions. This study was conducted using a convergent mixed-methods design. For the quantitative phase, the pre-test – post-test control group experimental design was used, while in the qualitative phase, a thematic analysis was performed using focus group discussion (FGD) as an additional evaluation. A total of 32 participants with a history of risky sexual activity and moderate-to-high early marriage intentions were recruited from a Senior High School in West Java during the COVID-19 pandemic using Proportional Random Sampling. Classically, the control group in this study was given standard interventions with education through socialization in one session. The intervention group was given psychoeducation and mind mapping in a 3-hour face-to-face session with an FGD. The data collected were analyzed using a paired-samples t test. This study shows that the provision of psychoeducation interventions combined with mind-mapping techniques was effective in influencing the knowledge and early marriage intentions of adolescents in West Java. The intervention succeeded in increasing the adolescents’ level of knowledge about marriage by 6.78% (ΔMean, 9.89) and reducing their early marriage intentions by 46.29% (ΔMean, 4.31), with significant differences from those of the adolescents in the control group (p = 0.004 and p = 0.001, respectively). Therefore, the combination of psychoeducation and mind mapping can reduce adolescents’ intentions to get married early and increase their knowledge about marriage. This study demonstrates that it can be used as an alternative preventive effort against early marriage.